More claims than land: Multi-facetted land use challenges in the port-city interface - Witte, Patrick; Wiegmans, Bart; Louw, Erik (Elsevier BV, 2025)
Port areas in densely urbanized areas are locations where the lack of development space increasingly limits growth possibilities, and competition for space between stakeholders with diverging interests and land use claims intensifies. The aim of our paper is to enrich the scientific discourse on the port-city interface by arguing for a more multi-facetted understanding of the port-city interface beyond arguments of economic efficiency, and what this implies for how land use conflicts materialize and are dissolved. Based on quantitative data we have analyzed the characteristics of the land use conflicts in two case study areas (the ports of Rotterdam and Amsterdam in the Netherlands) in more detail. Furthermore, we developed a framework that could contribute to mitigating the effects of the land use conflicts, and have qualitatively explored this through an analysis of port visions and annual reports of the port authorities. The findings suggest that, even though the net claims do not yet outnumber the available land, the cumulative effects of these diverging interests do, which suggests that the battle for space is about to intensify as there are more claims than land.
Keywords: Area development; Land use dynamics; Port-city interface; SDG 15 - Life on Land